2021
DOI: 10.1002/2211-5463.13265
|View full text |Cite
|
Sign up to set email alerts
|

Tomatidine provides mitophagy‐independent neuroprotection after ischemic injury

Abstract: Cerebral ischemia is one of the leading causes of human mortality and disability worldwide. The treatment of cerebral ischemia is refractory due to its short therapeutic window and lack of effective clinical drugs.Mitophagy, the autophagic elimination of damaged mitochondria, attenuates neuronal injury in cerebral ischemia, indicating the potential of mitophagy inducers as therapies for cerebral ischemia. We previously determined that, by enhancing autophagy flux, the steroidal alkaloid tomatidine can function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Kshirsagar published a second time a year later, this time using the amyloid precursor protein (APP) as a transfect for HT-22 cells (APP-HT22) [ 57 ]. Results are quite similar to the previously described article [ 56 ] albeit that TO (10µM) did not enhance the survival of APP-HT22 cells.…”
Section: Therapeutic Context— Solanum S(g)asmentioning
confidence: 99%
“…Kshirsagar published a second time a year later, this time using the amyloid precursor protein (APP) as a transfect for HT-22 cells (APP-HT22) [ 57 ]. Results are quite similar to the previously described article [ 56 ] albeit that TO (10µM) did not enhance the survival of APP-HT22 cells.…”
Section: Therapeutic Context— Solanum S(g)asmentioning
confidence: 99%
“…Studies have shown that tomatidine has a variety of health effects, such as anti-in ammatory, anti-atherosclerotic, and antibacterial 10 . Tomatidine has been reported to inhibit cancer cell growth 11 , and tomatidine can induce autophagy in damaged cells 12 . A number of studies have shown that tomatidine, an abundant steroidal alkaloid in Solanaceae, has pro-autophagy biological activity in vitro and in vivo for a variety of species.…”
Section: Introductionmentioning
confidence: 99%